Knowledge Level of DAGUSIBU in Pharmacy Department Students at Health Polytechnic of Tanjung Karang - Sembiring, Elma Viorentina; Hartati, Ani; Julaiha, Siti (Poltekkes Kemenkes Tanjung Karang, 2023)
There are many health problems due to lack of knowledge and understanding of how to use, store and dispose of drugs. The Indonesian Pharmacist Association (IAI) to design a program called DAGUSIBU (Get-Use-Save-Dispose). Information about DAGUSIBU is important to avoid giving wrong information from occupational pharmacy to patients. This study aims to determine Knowledge Level Profile of DAGUSIBU in Pharmacy Department Students in Health Polytechnic of Tanjung Karang 2022. This research was observational research design with a cross-sectional approach which was carried out from October to November 2022 involving 226 pharmacy students class of 2020 to 2022 in Health Polytechnic of Tanjung Karang. Data obtained by using an online questionnaire that had been tested for validity and reliability. In the aspect of getting medicine, the knowledge level pharmacy students 15.5% good, 38.9% sufficient, and 45.4% lacking. In the aspect of drug use, having a greater knowledge level of 11.1% is good; 44.7% sufficient; and 44.2% less. In the aspect of saving medicine, having a knowledge level of 9.3% is good; 40.3% sufficient; and 34.0% less. Bivariate analysis using ANOVA to find out differences of knowledge level among classes. The results of the ANOVA test showed a p-value of 0.112 so that it can be concluded that there is no significant difference in the level of DAGUSIBU knowledge between batches in Pharmacy students at Health Polytechnic of Tanjung Karang in 2022.